2018
DOI: 10.1038/s41598-018-35592-0
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between SOX2 and cytokine signaling in endometrial carcinoma

Abstract: Endometrial carcinoma is a cancer derived from oncogenesis of the regenerating uterine cavity, in which cytokine stimulation shapes cell differentiation and tissue remodeling. Expression of the stem cell factors SOX2, OCT4, NANOG, and MYC has been linked to tumor malignancy in several cancers. However, how these stem cell factors crosstalk with cytokine signaling to promote malignancy in endometrial carcinoma is still elusive. Here we report that the expression of SOX2 and MYC, but not that of OCT4 and NANOG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Third, our data demonstrated that the core stem gene SOX2 is the main target of HIF-dependent demethylase ALKBH5, which is involved in demethylation of downstream targets and further recruitment to m 6 A-modified sites. Our work in ECSCs revealed the relationship between HIFs and SOX2, which has been reported to be correlated with lymph node infiltration in EC 60 . In gastric cancer, SOX2 enhances HIF-1α promoter activity to regulate glucose metabolism 61 .…”
Section: Discussionsupporting
confidence: 60%
“…Third, our data demonstrated that the core stem gene SOX2 is the main target of HIF-dependent demethylase ALKBH5, which is involved in demethylation of downstream targets and further recruitment to m 6 A-modified sites. Our work in ECSCs revealed the relationship between HIFs and SOX2, which has been reported to be correlated with lymph node infiltration in EC 60 . In gastric cancer, SOX2 enhances HIF-1α promoter activity to regulate glucose metabolism 61 .…”
Section: Discussionsupporting
confidence: 60%
“…In gastrointestinal [8] and lung [9] MiNENs, genetic and immunohistochemical studies have suggested a common origin in the amphicrine but not other subtypes. In our case, a crude comparison of significant variants that appeared in the neuroendocrine component shows emerging JAK1, PRKAR1A, and SOX9 mutations, some of which have been loosely associated with a neuroendocrine phenotype in early studies of multiple tumors but could also be tissue specific or random events [10–13]. It would take comparisons with multiple other similar tumors and considerations of the variants that disappeared in evolution to reach definite conclusions.…”
Section: Discussionmentioning
confidence: 87%
“…Then, we obtained 133 significantly up-regulated genes from the dataset GSE13003, which was intersected with the downstream transcription factors and finally MYC was obtained (Figures 4B, C). Previous evidence has demonstrated that high expression of MYC is related to low overall survival rate of EC patients (11). Therefore, we speculated that LINC00470 may regulate downstream pathways through MYC.…”
Section: Linc00470 Binds To Myc Protein In Ec and Promotes The Binding Of Myc To Dnmt3amentioning
confidence: 87%
“…MYC is a known oncogene in human cancers, whereas its inhibition suppresses tumorigenesis (10). Furthermore, high expression of MYC may predict dismal overall survival rate of EC patients (11). Additionally, MYC can physically interact with DNA (cytosine-5)-methyltransferase 3a (DNMT3a), recruiting it to the promoter of microRNA-200b (miR-200b) to induce DNA hypermethylation (12).…”
Section: Introductionmentioning
confidence: 99%